Physiological response of cocoa (Theobroma cacao L. ) genotypes to drought - Suchithra, M.; Suma, B.; Minimol, J.S.; Mathew, Deepu; Santhosh Kumar, A.V. (Journal of Plantation Crops, 2022)
Drought is one of the major environmental stresses affecting crop productivity worldwide. Climate change is expected to result in a rise in the number and intensity of drought events in the coming decades, so climate-resilient crops that can withstand this stress are in high demand. There are few genotypes in cocoa where it can tolerate water deficit conditions. The objective of the current investigation was to evaluate the effect of drought stress on the photosynthetic and physiological parameters of six cocoa genotypes (Theobroma cacao L.) with two irrigation regimes (100% field capacity and 40% field capacity) under greenhouse conditions at Cocoa Research Station, Kerala Agricultural University, Thrissur. The effect of water deficit conditions on gas exchange and physiological parameters such as relative water content, membrane stability index, chlorophyll stability index, and chlorophyll content were evaluated. Drought stress conditions resulted in reduced photosynthetic rate, relative water content, chlorophyll content, chlorophyll stability and membrane stability. All genotypes revealed significant differences for most parameters with two irrigation regimes. Among the cocoa genotypes, P.IV 19.9, which is classified as a highly tolerant genotype, recorded better results for all the parameters studied under water deficit conditions at 40 per cent FC. The findings of this study support the classification of these genotypes as highly tolerant, tolerant, and susceptible. These parameters may be used as the most promising indicators to screen for drought tolerance in cocoa. The results of the study revealed that photosynthetic and physiological parameters have a significant role in imparting drought stress tolerance to cocoa. Furthermore, these selected drought-tolerant genotypes can be used in future crop improvement programmes in cocoa.